Table tilt versus pelvic tilt position for intrauterine resuscitation during spinal anaesthesia for caesarian section - Shahla Haleem; Neeraj K Singh; Shyam Bhandari; Dheeraj Sharma; S Hussain Amir (Wolters Kluwer Medknow Publications, 2011)
Background: This study was undertaken to compare the effects on intrauterine resuscitation by table tilt versus pelvic tilt position after spinal anaesthesia for Caesarian Section. Patients & Methods: Fifty ASA I and II patients who fulfilled the eligibility criteria were enrolled in the study and were divided into two groups: group W (Pelvic tilt with wedge under right hip and group L- (15 0 left lateral table tilt) and received spinal anaesthesia. The following parameters were recorded. Heart rate (HR), mean arterial pressure (MAP) at baseline, 2mins, 5 min and then 5 min thereafter. Mean height of block, Total no. of segments blocked, Onset Time of sensory block (in Minutes), ephedrine doses, incidence of hypotension & bradycardia, APGAR score at 1& 5 Minutes. Results : The decrease in MAP was much more in wedged position as compared to table tilt position also the incidence of hypotension was 40% in wedged position as compared to 12% in table tilt position. Mean height of block, Total no. of segments blocked, and boluses of inj. ephedrine used were more in the wedged position than in table tilt position. Conclusion: Wedge placement caused increased incidence of hypotension and higher blockade after spinal anaesthesia as compared to left lateral table tilt position, there was no adverse effects on foetus and patients tolerated wedge better than left lateral table tilt position. Also surgery was easier to perform after wedge placement.